2020
DOI: 10.1101/2020.03.12.988691
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plant-derived CO2mediates long-distance host location and quality assessment by a root herbivore

Abstract: Insect herbivores can use volatile and visual cues to locate and select suitable host plants from a distance. The importance of CO 2 , arguable the most conserved volatile marker of metabolic activity, is not well understood in this context, even though many herbivores are known to respond to minute differences in CO 2 concentrations. To address this gap of knowledge, we manipulated CO2 perception of the larvae of the western corn rootworm (Diabrotica virgifera virgifera; WCR) through RNA interference and stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 122 publications
(150 reference statements)
0
4
0
Order By: Relevance
“…Whether this finding means that the SvelGR3-encoding gene was truly lost and S. velatus thus lost the related ability remains unclear. A recent study on the larvae of a chrysomelid root herbivore, Diabrotica virgifera , showed that GR2 is responsible for the perception of plant-derived CO 2 and plays a crucial role in long-distance host location and assessment of the plant nutritional status ( Arce et al, 2020 ). Whether S. velatus GRs have similar physiological or behavioral functions is worth further study.…”
Section: Discussionmentioning
confidence: 99%
“…Whether this finding means that the SvelGR3-encoding gene was truly lost and S. velatus thus lost the related ability remains unclear. A recent study on the larvae of a chrysomelid root herbivore, Diabrotica virgifera , showed that GR2 is responsible for the perception of plant-derived CO 2 and plays a crucial role in long-distance host location and assessment of the plant nutritional status ( Arce et al, 2020 ). Whether S. velatus GRs have similar physiological or behavioral functions is worth further study.…”
Section: Discussionmentioning
confidence: 99%
“…It may also be possible to utilize knowledge of the factors influencing host plant establishment for management in the future. WCR larvae orient towards maize roots following CO 2 gradients and can detect concentrations as low as 2 mmol/mol [ 27 , 28 , 29 ]. In choice tests, significantly more neonate WCR larvae were attracted to synthetic CO 2 with a concentration of 11.2 mmol/mol than to growing maize with a CO 2 concentration of 1.36 mmol/mol [ 29 ].…”
Section: Disrupting Wcr Establishmentmentioning
confidence: 99%
“…3D). To assess silencing specificity, we measured the transcription of the putative CO2-receptor DvvGr2 (67). Feeding dsRNA targeting DvvGr43a did not change the transcript abundance of DvvGr2 (Fig.…”
Section: Independent Manipulation Of Benzoxazinoids and Sugars As Formentioning
confidence: 99%
“…Western corn rootworm larvae respond behaviorally to a wide variety of chemical cues, including CO2 (60), sugars and fatty acids (61,62), aromatic and terpene volatile organic compounds (63,64), conjugated phenolic acids (65) and benzoxazinoids (66). The emerging picture is that these chemicals likely allow western corn rootworm larvae to locate plant roots from a distance (67), to discriminate between plants of different quality (63)(64)(65)68), and to identify and feed on the most nutritious roots (66,69). Several in vitro experiments also suggest that the western corn rootworm can integrate multiple chemical cues for host finding and acceptance (61), hinting at the substantial sensory capacity of this specialist root feeder.…”
Section: Introductionmentioning
confidence: 99%